Preterm-born children, screen time, and spectacle wear in the Longitudinal Preterm Outcome Project: a cohort study - Iyer, V.; de Kroon, M. L. A.; Klaver, C. C. W.; Reijneveld, S. A. (Frontiers in Pediatrics, 2025)
IntroductionPreterm born children are at a higher risk for refractive errors. A long duration of screen time and activities with short working distance (≤30 cm) may further add to the increased risk. The aim of this study was to assess the separate and combined effects of preterm birth and screen time on spectacle wear among 5-year-olds and adolescents.MethodsWe analyzed data from the community-based preterm cohort study, part of the Longitudinal Preterm Outcome Project (LOLLIPOP). Early preterm-born (EP < 32 weeks), moderately-late preterm-born (MLP 32–36 weeks) and full-term born (FT 38–42 weeks) children were followed. Spectacle wear and screen time were assessed by questionnaire at the age of 5 (n = 1,515) and at adolescence, ages 13–16, for a subsample (n = 227).ResultsAt age 5, the prevalences of spectacle wear were 7.8%, 7.6% and 3.2%, for EP, MLP, and FT children, respectively (p = 0.007); the risk of spectacle wear decreased by 7% for each additional week of gestational age. In adolescence, prevalences were 36.6%, 20.8% and 22.4%, for EP, MLP, and FT children, respectively (p = 0.12). We found no relationship between screen-time and spectacle wear or a combined effect with preterm birth at age 5 or adolescence.ConclusionsEP and MLP children have a significantly increased risk of spectacle wear at age 5, but not significantly at adolescence. At that age, the prevalences of spectacle wear were generally higher. We found no evidence for an association of screen time preterm birth with spectacle wear, and neither an impact of screentime on such an association.